The Relationship Between Leverage and Profitability: The Role of Tax Depreciation Allowances - Nicos Koussis; Francesco Menoncin; Paolo M. Panteghini (CESifo GmbH, 2025)
We extend Trade-Off Theory (TOT) by assuming that EBITDA (Earnings Before Interest, Taxes, Depreciation, and Amortization), rather than EBIT (Earnings Before Interest and Taxes), follows a Geometric Brownian Motion (GBM), and we thus consider the role of tax depreciation allowances (TDA) in firms' leverage decisions. Our model also accounts for the possibility of a sudden stop in a firm's operations and thus incorporates the impact of finite firm and depreciation tax allowances on leverage. We show that TDA act as a complement to debt leverage, generating a negative leverage-profitability relationship over a wide range of plausible parameters, consistent with empirical evidence. However, our model also predicts that this relationship may weaken in low-tax environments or at moderate levels of volatility, and may even turn positive under very high volatility. The model retains the standard TOT predictions regarding the sensitivity of leverage to volatility, taxes, growth, and bankruptcy costs, while incorporating the effects of TDA and a finite firm horizon. Furthermore, our analysis highlights that policymakers can influence corporate capital structure through both tax rates and TDA. To implement effective policy, they should also account for the volatility of the business environment.
Keywords: G32; H25; 330; capital structure; contingent claims; corporate taxation; profitability; trade-off model